FACTORS AFFECTING THE INVESTMENT ENVIRONMENT AND ITS FINANCING SOURCES (Scientific Journal of Actuarial Finance and Accounting, 2024)
This article explores the various factors that can affect the investment environment and the sources of financing available to investors. The investment environment is influenced by a range of factors, including economic conditions, political stability, regulatory environment, and market dynamics. These factors can impact the risk and return profile of investments, as well as the overall attractiveness of a particular market.